Pengembangan Makanan Tradisional Apem Kesesi Menggunakan Metode Quality Function Deployment (QFD) dan Konsep Green Product Sebagai Upaya Meningkatkan Kualitas Produk - Beta Arya Ash Shidik; Yohandika Tri Apriliyanto; Vidya Renatha Sari (Universitas Islam Raden Rahmat, Malang, 2024)
Apem kesesi is a traditional wet cake food in Pekalongan district. Apem kesesi cake has the problem of not being long-lasting, the packaging and appearance of the product is less attractive, less hygienic, impractical and the taste is not suitable for the younger generation. Therefore, it is necessary to develop apem kesesi products according to needs to improve product quality. Apem kesesi product development uses the quality faction deployment (QFD) method and the green product concept. Based on survey results, consumers want apem kesesi products that are hygienic, practical, unique, have attractive packaging and are durable. The main ingredient for making apem cake is rice flour. Add tapioca flour to give the apem cake a chewy texture, palm sugar to produce a distinctive taste and aroma, then vanilla to strengthen the taste, and sodium benzoate as a preservative. The product packaging design consists of primary packaging and secondary packaging. Based on validation tests and different tests, the results showed that the product design developed met consumer needs and was better than existing products.